The culture of caring for low birth weight infants at home after treatment: An ethnographic study from Indonesia - Sri Intan Rahayuningsih; Yeni Rustina; Yati Afiyanti; Tris Eryando (Jurnal Keperawatan Padjadjaran, 2024)
Background: Caring for low birth weight (LBW) babies is a challenge for parents, especially after being discharged from the hospital, to continue the care provided by professional nurses. Culture can influence how parents behave and decide to keep babies healthy. Purpose: This study examined the culture that influences mothers in Aceh, Indonesia, to care for LBW infants at home following hospital treatment. Methods: This study used an ethnographic design that involved ten participants consisting of mothers who had an LBW infant after receiving hospital care, a grandmother, a midwife, and health cadres. The data were collected using focus group